THE EFFECT OF SOCIAL MEDIA MARKETING AND BRAND IMAGE ON LOYALTY WITH TRUST AS A MEDIATION VARIABLE - Yunissinta, Punky; Fitriani, Endah Nur (Journal of Islamic enterpreneurship and Management, 2021)
This study aims to examine the effect of social media marketing and brand image on loyalty with trust as a mediating variable. This research used quantitative research. This study used primary data by distributing questionnaires using google forms which were distributed at BRI Syariah KCP Magelang. The data were analyzed using SPSS tools. The population in this study were BRI Syariah KCP Magelang customers and 100 customers were used as the sample. The results of this study show that social media marketing, brand image, and trust affect loyalty. Trust can mediate social media marketing on loyalty and trust can mediate brand image on loyalty.